Superhydrophobic and Antireflective Properties of the Hierarchically Nanotextured Glass Surfaces - Gwon, Hyo Jin; Shim, Young-Seok; Nahm, Sahn; Yoon, Seok-Jin; Jang, Ho Won (AMER SCIENTIFIC PUBLISHERS, 2015)
We report that a facile dry etching process using silica beads can be used to fabricate a hierarchically nanotextured (HNT) glass with the self-cleaning and antireflection properties. HNT glass gives rise to a high water contact angle (> 158 degrees) and very efficient cleaning-out of dust with water drops. The maximal transmittance of the etched glass at a normally incident light can reach similar to 90% with the low reflectivity (<4%) in the visible wavelengths. Furthermore, we provide the video-based evidence for the effectiveness of the superhydrophobic glass in removing dust from the surface. This simple, low-cost, and efficient way of producing glass with superhydrophobic and antireflective properties presented in this work would have a powerful applied potential in various technological areas.